Role of School Counselling in India Opportunities and Challenges - Venkatesan, M.; Rohatgi, Anubha (JOURNAL OF INDIAN EDUCATION, 2016)
The liberalised economy, growing market pressure, change in curriculum, unpredictable future, etc., has made it really tough for Indian school children to perform. The role of schools in channelising energy of their wards and preparing them to face the competitive world, besides contributing productively in the society are crucial. Unfortunately, the growth of school counselling in India is not properly addressed. Indeed, the services are rendered only on demand basis, and for the remaining time, school counsellors’ services are utilised for inconsequential purposes. Sensitisation of counselling at the school level is not great as evident from the case study of schools in Delhi-NCR. This is because the services offered by school counsellors are restricted to vocational counselling and to some extent with behavioural issues. However, the school policy is being reviewed in order to make counselling ‘compulsory sessions’ in schools. This move will bring in a healthy atmosphere and confidence in school children to face the competitive world. This study is aimed at addressing the aforesaid issues in detail in order to deliberate on the unrelenting challenges posed by various groups and how to handle them meaningfully.